Cooperation of two ADAMTS metalloproteases in closure of the mouse palate identifies a requirement for versican proteolysis in regulating palatal mesenchyme proliferation - Enomoto, Hiroyuki (Company of Biologists, 2010)
We have identified a role for two evolutionarily related, secreted metalloproteases of the ADAMTS family, ADAMTS20 and ADAMTS9, in palatogenesis. Adamts20 mutations cause the mouse white-spotting mutant belted (bt), whereas Adamts9 is essential for survival beyond 7.5 days gestation (E7.5). Functional overlap of Adamts9 with Adamts20 was identified using Adamts9(+/–);bt/bt mice, which have a fully penetrant cleft palate. Palate closure was delayed, although eventually completed, in both Adamts9(+/–);bt/+ and bt/bt mice, demonstrating cooperation of these genes. Adamts20 is expressed in palatal mesenchyme, whereas Adamts9 is expressed exclusively in palate microvascular endothelium. Palatal shelves isolated from Adamts9(+/–);bt/bt mice fused in culture, suggesting an intact epithelial TGFβ3 signaling pathway. Cleft palate resulted from a temporally specific delay in palatal shelf elevation and growth towards the midline. Mesenchyme of Adamts9(+/–);bt/bt palatal shelves had reduced cell proliferation, a lower cell density and decreased processing of versican (VCAN), an extracellular matrix (ECM) proteoglycan and ADAMTS9/20 substrate, from E13.5 to E14.5. Vcan haploinsufficiency led to greater penetrance of cleft palate in bt mice, with a similar defect in palatal shelf extension as Adamts9(+/–);bt/bt mice. Cell density was normal in bt/bt;Vcan(hdf)(/+) mice, consistent with reduced total intact versican in ECM, but impaired proliferation persisted in palate mesenchyme, suggesting that ADAMTS-cleaved versican is required for cell proliferation. These findings support a model in which cooperative versican proteolysis by ADAMTS9 in vascular endothelium and by ADAMTS20 in palate mesenchyme drives palatal shelf sculpting and extension.